Biomimetic Hydrogel Applications and Challenges in Bone, Cartilage, and Nerve Repair - Yanbing Gao; Xiaobo Zhang; Haiyu Zhou (MDPI AG, 2023)
Tissue engineering and regenerative medicine is a highly sought-after field for researchers aiming to compensate and repair defective tissues. However, the design and development of suitable scaffold materials with bioactivity for application in tissue repair and regeneration has been a great challenge. In recent years, biomimetic hydrogels have shown great possibilities for use in tissue engineering, where they can tune mechanical properties and biological properties through functional chemical modifications. Also, biomimetic hydrogels provide three-dimensional (3D) network spatial structures that can imitate normal tissue microenvironments and integrate cells, scaffolds, and bioactive substances for tissue repair and regeneration. Despite the growing interest in various hydrogels for biomedical use in previous decades, there are still many aspects of biomimetic hydrogels that need to be understood for biomedical and clinical trial applications. This review systematically describes the preparation of biomimetic hydrogels and their characteristics, and it details the use of biomimetic hydrogels in bone, cartilage, and nerve tissue repair. In addition, this review outlines the application of biomimetic hydrogels in bone, cartilage, and neural tissues regarding drug delivery. In particular, the advantages and shortcomings of biomimetic hydrogels in biomaterial tissue engineering are highlighted, and future research directions are proposed.